The study of cancer cell in stromal environment through induced pluripotent stem cell–derived mesenchymal stem cells. Issue 8 (6th June 2022) - Loh, Jit-Kai; Wang, Mong-Lien; Cheong, Soon-Keng; Tsai, Fu-Ting; Huang, Shu-Huei; Wu, Jing-Rong; Yang, Yi-Ping; Chiou, Shih-Hwa; Ong, Alan Han-Kiat
Abstract : Background: The development of mesenchymal stem cells (MSCs) has gained reputation from its therapeutic potential in stem cell regeneration, anti-inflammation, tumor suppression, and drug delivery treatment. Previous studies have shown MSCs have both promoting and suppressing effects against cancer cells. While the limitation of obtaining a large quantity of homologous MSCs for studies and treatment remains a challenge, an alternative approach involving the production of MSCs derived from induced pluripotent stem cells (iPSCs; induced MSCs [iMSCs]) may be a promising prospect given its ability to undergo prolonged passage and with similar therapeutic profiles as that of their MSC counterparts. However, the influence of iMSC in the interaction of cancer cells remains to be explored as such studies are not well established. In this study, we aim to differentiate iPSCs into MSC-like cells as a potential substitute for adult MSCs and evaluate its effect on non-small-cell lung cancer (NSCLC). Methods: iMSCs were derived from iPSCs and validated with reference to the International Society of Cellular Therapy guidelines on MSC criteria. To create a stromal environment, the conditioned medium (CM) of iMSCs was harvested and applied for coculturing of NSCLC of H1975 at different concentrations. The H1975 was then harvested for RNA extraction and subjected to next-generation sequencing (NGS) for analysis. Results: The morphology of iMSCs-CM–treated H1975 was different from an untreated H1975. Our NGS data suggest the occurrence of apoptotic events and the presence of cytokines from H1975's RNA that are treated with iMSCs-CM. Conclusion: Our results have shown that iMSCs may suppress the growth of H1975 by releasing proapoptotic cytokines into coculture media. Using iPSC-derived MSC models allows a deeper study of tumor cross talk between MSC and cancer cells that can be applied for potential future cancer therapy.